Charisma Production Dance Studio Management - Aisyah Novitasari (Jurnal Seni Tari, 2024)
The purpose of this writing is to understand the management of the Charisma Production Studio as a studio that only operates and focuses on the entertainment/business sector. The research method used is a descriptive qualitative research method. In this research, the main data source is qualitative research, and collection techniques using observation, interviews, and documentation. Data analysis by data reduction, data presentation, and conclusion.  The results of this research are the background of the Charisma Production Studio. This studio was established in 2003, was founded and chaired by Mr. Haris, is located in Surabaya, and has high popularity. The management function at the Charisma Studio is to regulate the running of all aspects of the Charisma Studio's organizational lines and marketing methods at the Charisma Production Studio. Conclusion The marketing system of the Charisma Studio, which is a studio following the business sector, keeps up with the times, maintains quality and quantity, is selective in choosing dancers, and does not escape the already highly-experienced Charisma Studio, these aspects create its branding. Charisma Studio, because this is what makes Charisma Studio considered a good and quality studio among studios in general